Pengaruh Inovasi Produk, Packaging dan Harga Terhadap Kepuasan Pelanggan Pada Green House Kandang Melon Kediri - Isma D, M Pramudya; Buniarto, Edwin Agus; Wahyu K, Brahma (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the effect of product innovation, packaging, and price on customer satisfaction at Green House Kandang Melon Kediri. This research employs a quantitative approach with a causal associative design. The population consists of customers who have purchased products from Green House Kandang Melon Kediri, with 100 respondents selected using purposive sampling. Primary data were collected through questionnaires measured using a five-point Likert scale. Data analysis was conducted using multiple linear regression with the assistance of SPSS software, preceded by validity, reliability, and classical assumption tests. The results indicate that product innovation has a positive and significant effect on customer satisfaction. Packaging also shows a positive and significant effect and is identified as the most dominant variable influencing customer satisfaction. In contrast, price has a negative and significant effect, indicating that price increases not aligned with perceived value may reduce customer satisfaction. Simultaneously, product innovation, packaging, and price have a significant effect on customer satisfaction. These findings suggest that an integrated marketing strategy focusing on continuous product innovation, attractive and functional packaging, and appropriate pricing is essential to enhance customer satisfaction in agribusiness enterprises.